Identification of flood impacts on construction sites/ Norazlin Mat Salleh ... [et al.] - Mat Salleh, Norazlin; Mamter, Shahela; Syed Jamalulil, Syarifah Nur Nazihah; Saberi, Mohd Hafiz; Mohamad Fadzili, Nurul Iman (Universiti Teknologi MARA, Perak, 2024)
Flooding is an unexpected phenomenon that happens throughout the year in Malaysia and has become very common. The yearly recurrence of floods has had a significant influence on the lives of humans and other living beings specifically at the construction sites. Due to the negative impact of floods, awareness must be given careful consideration. The purpose of this research is to identify the impact of the flood occurrence on the construction sites. The initial research begins with a literature review from various scholars on key areas of flood and the impact of flood on construction sites. The next stage was of obtaining the data was though primary data. The research instrument was a set of questionnaires. The questionnaires were divided into two sections A – Demographic Questions and B – The impacts of flood. Questions for Section B used five Likert Scales strongly agree to strongly disagree. All the data were analysed using SPSS software, on the frequency and descriptive analysis. The respondents were contractors in Grade 7 (G7) registered with the Construction Industry Development Board (CIDB) in Selangor state. A total of 146 respondents participated in this research. This research identified five impacts of flood occurrence in construction sites. There are reconstruction and maintenance of the building structure, safety of labour, the cost of reconstruction, the defects to the building structure, and construction delays. All the construction stakeholders need to be aware and prepared with the flood occurrence to avoid from losses and delays to construction project.